Feasibility and safety of a self-developed sleeve for the endoscopic removal of refractory foreign body incarceration - Yu, Guangqiu; Li, Li; Zhang, Yirui; Zhong, Xiaohuan; Wang, Jing; Jiang, Ling; Hu, Duanmin; Zhou, Weixia (Frontiers in Surgery, 2023)
Objective: This study aimed to assess the feasibility and safety of a novel self-designed sleeve for the endoscopic removal of refractory incarcerated foreign body in the upper gastrointestinal tract (UGIT). Methods: A interventional study was conducted between June and December 2022. Sixty patients who underwent endoscopic removal of refractory incarcerated foreign body from the UGIT were randomly allocated to the self-developed sleeve and the conventional transparent cap. The study evaluated and compared the operation time, successful removal rate, new injury length at the entrance of the esophagus, new injury length at the impaction site, visual field clarity, and post-operative complications between the two groups. Results: The success rates of the two cohorts in foreign body removal display no significant discrepancy (100% versus 93%, P = 0.529). Nevertheless, the novel overtube-assisted endoscopic foreign body removal methodology culminated in a significant reduction in removal duration (40 (10, 50) minutes vs. 80 (10, 90) minutes, P = 0.01), reduction in esophageal entrance traumas (0 (0, 0) mm vs. 4.0 (0, 6) mm, P < 0.001), mitigation in injuries at the foreign body incarceration location (0 (0, 2) mm vs. 6.0 (3, 8) mm, P < 0.001), an enhanced visual field (P < 0.001), and a decrement in post-operative mucosal bleeding (23% versus 67%, P < 0.001). The self-developed sleeve effectively negated the advantages of incarceration exclusion during removal. Conclusion: The study findings support the feasibility and safety of the self-developed sleeve for endoscopic removal of refractory incarcerated foreign body in the UGIT, with advantages over the conventional transparent cap.